A Health Literacy Model for Healthy Eating, Emotional Health, and Physical Activity among Village Health Volunteers in Bang Yai District, Nonthaburi Province - Namawiroj, Panote; Swangsoonthonwes, Pilas; Komonpanich, Pratya; Noykumsin, Suwaree (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: 1) examine the current status of health literacy development in promoting eating behavior, emotional management, and exercise among Village Health Volunteers (VHVs) in Bang Yai District, Nonthaburi Province; 2) analyze factors influencing health-promoting behaviors in these three dimensions; and 3) propose a model for health literacy development to enhance health promotion practices among VHVs.           This study employed a descriptive research design. The population consisted of 210 Village Health Volunteers who attended the annual VHV meeting in 2024. The sample size was determined using Taro Yamane’s formula, yielding 140 participants. Data were collected using a structured questionnaire comprising three parts: personal characteristics; management processes for health literacy development based on the PDCA cycle (Plan–Do–Check–Act) with 16 items; and health literacy behaviors in promoting eating, emotional health, and exercise based on the V-SHAPE framework (Access, Understand, Interact/Exchange, Decide, Change Behavior, Share/Empower) with 12 items. The instrument demonstrated content validity (IOC = 0.67–1.00) and high reliability (Cronbach’s alpha = 0.95). Data were collected from January 1–31, 2025, with a response rate of 100 percent. Data were analyzed using descriptive statistics (percentage, mean, standard deviation) and inferential statistics including multiple regression analysis.           The findings revealed that the overall management process for health literacy development was at a moderate level (x̄ = 3.21, S.D. = .52). Among the PDCA components, the “Act” dimension (continuous improvement) showed the highest mean score at a high level (x̄ = 3.75, S.D. = .41), while the “Check” dimension ranked lowest but remained at a moderate level. Regarding health literacy behaviors based on the V-SHAPE framework, the overall level was moderate (x̄ = 2.54, S.D. = .63). The highest mean was found in the Access dimension, followed by Interact/Exchange, whereas Share/Empower had the lowest mean score.           Multiple regression analysis indicated that the “Check” (B = .58, Beta = .492, p < .001) and “Act” (B = .34, Beta = .224, p = .005) components significantly predicted health literacy behaviors. The model demonstrated a multiple correlation coefficient (R) of .65 and an adjusted R² of .42, indicating that management processes explained 42 percent of the variance in health literacy promotion behaviors. The predictive equation in raw score form was: Ŷ = .59 + (.58 Check) + (.34 Act).          The results suggest that systematic monitoring and continuous improvement mechanisms are critical determinants in strengthening health literacy behaviors among VHVs. Therefore, an effective model for health literacy development should emphasize evaluation, reflective practice, and sustainable improvement processes to enhance eating behavior, emotional well-being, and exercise promotion at the community level.